Role of androgen receptor splice variant 7 (AR-V7) in prostate cancer resistance to 2(nd) generation androgen receptor signaling inhibitors - Zhu, Yezi (Oncogene, 2020)
The role of truncated androgen receptor splice variant-7 (AR-V7) in prostate cancer biology is an unresolved question. Is it simply a marker of resistance to 2(nd) generation androgen receptor signaling inhibitors (ARSi) like Abiraterone Acetate (Abi) and Enzalutamide (Enza) or a functional driver of lethal resistance via its ligand-independent transcriptional activity? To resolve this question, the correlation between resistance to ARSi and genetic chances and expression of full length AR (AR-FL) vs. AR-V7 were evaluated in a series of independent patient-derived xenografts (PDXs). While all PDXs lack PTEN expression, there is no consistent requirement for mutation in TP53, RB1, BRCA2, PIK3CA, or MSH2, or expression of SOX2 or ERG and ARSi-resistance. Elevated expression of AR-FL alone is sufficient for Abi- but not Enza-resistance, even if AR-FL is gain-of-function (GOF) mutated. Enza-resistance is consistently correlated with enhanced AR-V7 expression. In vitro and in vivo growth responses of Abi-/Enza-resistant LNCaP-95 cells in which CRISPR-Cas9 was used to knockout AR-FL or AR-V7 alone or in combination were evaluated. Combining these growth responses with RNAseq analysis demonstrates that both AR-FL and AR-V7 dependent transcriptional complementation are needed for Abi/Enza resistance.